1989
DOI: 10.1017/s1446788700030846
|View full text |Cite
|
Sign up to set email alerts
|

Maximal subgroups and the Jordan-Hölder Theorem

Abstract: In this note we present a general Jordan-Holder type theorem for modular lattices and apply it to obtain various (old and new) versions of the Jordan-Holder Theorem for finite groups. Isbell [ 10] has observed that the Jordan-Holder Theorem may be derived from the Zassenhaus Theorem, and that this yields a uniqueness statement for the correspondence given by the Jordan-Holder Theorem. This result, however, does not give the various versions of the Jordan-Holder Theorem for finite groups that have received some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Nevertheless, the arguments we have presented here to prove Theorem A(a) are exactly those to prove that M is an M-set. It must be observed that in [13] it is proved that the bijection mentioned in Theorem A(a) is unique.…”
Section: Is X-frattini If and Only If M^/m^^ Is X-frattini; (Iii) / /mentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, the arguments we have presented here to prove Theorem A(a) are exactly those to prove that M is an M-set. It must be observed that in [13] it is proved that the bijection mentioned in Theorem A(a) is unique.…”
Section: Is X-frattini If and Only If M^/m^^ Is X-frattini; (Iii) / /mentioning
confidence: 99%
“…Given a modular lattice if, J. Lafuente in [13] introduced the concept of M-set in 5£ and he proved a general Jordan-Holder theorem in modular lattices with an M-set.…”
Section: Is X-frattini If and Only If M^/m^^ Is X-frattini; (Iii) / /mentioning
confidence: 99%
See 1 more Smart Citation
“…Our primary objective is to generalise further the version of the Jordan-Hölder Theorem for chief series of L established in [4]. Our result could probably be obtained from [2], but we prefer to follow the approach adopted for groups (though in a more general context) in [1] as interesting results and concepts are obtained on the way.…”
Section: Introductionmentioning
confidence: 99%